A Novel Three Phase Multilevel Inverter with Single Dc Link For Induction Motor Drive Applications - A. Ramesh; O. Chandra Sekhar; M. Siva Kumar (International Journal of Electrical and Computer Engineering (IJECE), 2018)
All industrial drives need a controlled output and it can be achieved by controlling the input supply. In this regard, the inverter circuit plays an important role in the applications of industrial drives. The industrial drives are operated at high rated power and the conventional inverters cannot be applicable for high power demands because of the large dV/dt (rate of change of voltage) and more switching losses. Therefore, multilevel inverters are introduced for high power-medium voltage applications. For all AC drives the MLIs are reliable in operation. This MLI topology also reduces the harmonics and bearings stress of a motor with low dV/dt. In most applications multilevel inverters are used because we can get more number of voltage levels. To increase the number of voltage levels, circuit needs to have more switches. But, we have to optimize the switch count and switching operations. The power level of the inverter is limited due to high currents and stress. In this paper, we proposed a new circuit topology which enables the switches to be active at different voltage levels, causes reduction of the switching losses and also increases the efficiency of the inverter. In this we have presented two configurations for an eleven level MLI for three phase induction motor drive application. In this an individual DC source is connected for each bridge circuit of each phase in one configuration and only one common DC link is used for three phases in another configuration. With this the size, cost and complexity could be decreased. In both the configurations the controlled output of the inverter is connected to the induction motor drive. The circuits are modeled using Matlab/simulink software and corresponding output waveforms are analyzed for both configurations.